Integrated framework to structurally model unreinforced masonry Italian medieval churches from photogrammetry to finite element model analysis through heritage building information modeling. (15th August 2021) - Pirchio, David; Walsh, Kevin Q.; Kerr, Elizabeth; Giongo, Ivan; Giaretton, Marta; Weldon, Brad D.; Ciocci, Luca; Sorrentino, Luigi
Highlights: Integrated framework from historic building information modeling to finite element method modeling. Application of linear modal response spectrum analysis to a complex unreinforced masonry medieval church case study. Identification of local collapse mechanism via finite element method analysis. Application of stiffness adaptation analysis to a complex unreinforced masonry medieval church case study. Abstract: A novel, integrated framework is proposed to assess the vulnerability of a case study unreinforced masonry (URM) Italian church by applying interacting modern tools including unmanned aircraft systems (UAS), "structure from motion" (SfM) photogrammetric survey equipment and software, and finite element method (FEM) analysis software in a complete heritage building information model (HBIM). The FEM model was used to perform both a modal response spectrum analysis and a validation pushover using stiffness adaptation analysis (SAA) to investigate the global behavior of the church and to identify the most critical local mechanisms for collapse potential. Once the most vulnerable components of the church were identified, macro-block analysis was used to estimate the capacity of these collapse mechanisms. Macro-block analysis is well established in the field and was proposed for use as one step in the proposed integrated framework with the aim of providing a holistic methodology that is sophisticated enough to identify the most vulnerable elements of URM churches, but also practical and efficient enough to be applied by practitioners. Traditionally, obtaining the necessary geometric information to correctly conduct the macro-block analysis of such complex buildings requires time-demanding and expensive surveying campaigns. Furthermore, accurately and precisely identifying the local failure mechanisms most influential to macro-block behavior is numerically demanding. The novelty of the current research detailed herein regards a proposed comprehensive seismic vulnerability analysis of historic URM churches with increased efficiency and accuracy of surveying and capacity modeling using modern tools in a fashion approachable by practitioners.